2005
DOI: 10.2527/2005.83122908x
|View full text |Cite
|
Sign up to set email alerts
|

Body condition score at parturition and postpartum supplemental fat effects on cow and calf performance1

Abstract: Three-year-old Angus x Gelbvieh beef cows nutritionally managed to achieve a BCS of 4 +/- 0.07 (479.3 +/- 36.3 kg of BW) or 6 +/- 0.07 (579.6 +/- 53.1 kg of BW) at parturition were used in a 2-yr experiment (n = 36/yr) to determine the effects of prepartum energy balance and postpartum lipid supplementation on cow and calf performance. Beginning 3 d postpartum, cows within each BCS were assigned randomly to be fed hay and a low-fat control supplement or supplements with either high-linoleate cracked safflower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
62
3
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 35 publications
13
62
3
7
Order By: Relevance
“…In a dairy cattle study, Loker et al (2012) found an unfavourable genetic correlation between BCS and milk production that increased as the lactation period progressed: the higher the milk production, the worse the body condition of the cow. Conversely, Lake et al (2005) found no significant effect of cow BCS on the calf weaning weight.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a dairy cattle study, Loker et al (2012) found an unfavourable genetic correlation between BCS and milk production that increased as the lactation period progressed: the higher the milk production, the worse the body condition of the cow. Conversely, Lake et al (2005) found no significant effect of cow BCS on the calf weaning weight.…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, the existing evidence on the connection between BCS and pregnancy rate is controversial. Lake et al (2005) conducted a study with crossbred cattle and reported increased pregnancy rate in cows with high BCS, whereas Mulliniks et al (2012) found that BCS had no effect on the pregnancy rate. Furthermore, little is known about the variability of BCS in beef cows and whether such differences are heritable.…”
Section: Introductionmentioning
confidence: 99%
“…O peso vivo do animal é um indicador limitado para esse contexto por ter grande variabilidade entre raças e até mesmo entre rebanhos, além de ser uma medida que necessita de infraestrutura e deslocamento dos animais para ser aferida. Lake et al (2005) ressaltaram que o ECC é um indicador das reservas de energia na forma de tecido muscular e/ou adiposo que pode ser usado para suportar os processos fisiológicos durante períodos de aumento da demanda metabólica. O acúmulo de gordura corporal ocorre quando a ingestão de nutrientes é maior que as exigências para mantença e produção (Wettemann & Bossis, 1999;Lake et al, 2004) e a mobilização quando os animais se encontram em balanço energético negativo (Lake et al, 2004), ou seja, quando a ingestão de energia é menor que a demanda.…”
Section: Resultsunclassified
“…O acúmulo de gordura corporal ocorre quando a ingestão de nutrientes é maior que as exigências para mantença e produção (Wettemann & Bossis, 1999;Lake et al, 2004) e a mobilização quando os animais se encontram em balanço energético negativo (Lake et al, 2004), ou seja, quando a ingestão de energia é menor que a demanda. O ECC ainda é mencionado ao parto como o principal fator determinante do intervalo partoprimeiro cio e taxa de prenhez em vacas multíparas (Richardset al, 1986;Selk et al, 1988;Spitzer et al, 1995;Lake et al, 2005) e um confiável indicador do desempenho reprodutivo pós-parto em primíparas (Wettemann & Bossis, 1999;Morrison et al, 1999;DeRouen et al, 1994).…”
Section: Resultsunclassified
See 1 more Smart Citation